2020
DOI: 10.1109/tte.2020.3010003
|View full text |Cite
|
Sign up to set email alerts
|

Power Distribution Algorithm and Steady-State Operation Analysis of a Modular Multiactive Bridge Converter

Abstract: Voltaje de la fuente o carga conectada en un puerto v k V Voltaje instantáneo del puente del módulo k v p V v ac reflejado al lado del primario del transformador v A,k V Voltaje drenador-fuente del MOSFET s3 en módulo kth v L k V Voltaje instantáneo en la inductancia del módulo k v ac V Voltaje instantáneo del bus AC XVIII Acrónimos Acrónimos ADC Análogo a Digital AMR Anisotropic Magneto Resistive CA Corriente alterna (Alternating current) CC Corriente continua (Direct Current) CMP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Furthermore, to bypass the idle source port, a bypass switch can be added in parallel with the corresponding transformer. Multiport DAB converters in [218] and [219] are constructed with an array of modules, where each module is based on active full bridges and independent transformers and connects to one port. This approach allows for full isolation and hot connection/disconnection of modules due to many transformers.…”
Section: ) Multiport Dab/dab3mentioning
confidence: 99%
“…Furthermore, to bypass the idle source port, a bypass switch can be added in parallel with the corresponding transformer. Multiport DAB converters in [218] and [219] are constructed with an array of modules, where each module is based on active full bridges and independent transformers and connects to one port. This approach allows for full isolation and hot connection/disconnection of modules due to many transformers.…”
Section: ) Multiport Dab/dab3mentioning
confidence: 99%
“…Many other topologies with different numbers of ports and power components are derived from the basic topology in Figure 2, for different proposes and applications, such as resonant MAB converters [130][131][132][133], and modular multi-active bridge (MMAB) converters [147][148][149][150]. These derived topologies are discussed further in the last section of the paper.…”
Section: Topology Of the Mab Convertermentioning
confidence: 99%
“…Control-level decoupling approaches can be applied to attenuate the interactions [148]. An iterative algorithm is proposed in [147] and applied to solve the nonlinear control equations and obtain the desired values of phase shifts (control inputs) to have independent power flow control. In one study [150], a dq-frame representation of the active power transfers is demonstrated, and the power flow decoupling term is derived to be implemented using feedforward in the control system.…”
mentioning
confidence: 99%
“…With the development of more electric aircraft (MEA) and all electric aircraft (AEA), the type and quantity of electrical equipment on-board are increasing rapidly [1], and the power grid structure has also become more complex [2]. The problem of power distribution will arise [3].…”
Section: Introductionmentioning
confidence: 99%